Tribocorrosion behavior of Al-based amorphous coatings prepared by different spraying methods - Jiachi Yuan; Zhiyuan Jing; Zhibin Zhang; Weiyan Lu; Suode Zhang; Yanhai Cheng; Xiubing Liang (Journal of Materials Research and Technology)
The correlation between the wear behavior of three types of Al-based amorphous coatings prepared by low-temperature high-velocity oxygen fuel (LT-HVOF), high-velocity air fuel (HVAF) and cold spraying (CS), and the corrosion behavior of the coatings has been investigated through friction and wear tests under dry friction and 3.5 wt% NaCl solution condition. In the 3.5 wt% NaCl solution, the lubricating effect significantly reduces the friction effect, reducing the coating's wear rate relative to dry friction conditions. In polarized friction conditions, the LT-HVOF coating exhibited passivation characteristics, while the HVAF coating demonstrated a wear rate half that of 34CrMo1A steel, showcasing superior corrosion and wear resistance. In corrosion-wear coupling, the promotion effect of wear on corrosion becomes more apparent.